2020
DOI: 10.1002/mp.14001
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Dosimetric characterization of the dynamic beam flattening MLC sequence on a ring shaped, Jawless Linear Accelerator with double stacked MLC

Abstract: Purpose To characterize the dosimetric features and limitations of the dynamic beam flattening (DBF) on the Halcyon 2.0 linear accelerator (Varian Medical Systems). Methods A predefined multi‐leaf collimator (MLC) sequence was introduced and used to flatten the 6 MV flattening filter free (FFF) beam on the Halcyon 2.0. Dosimetric characterizations of the flattened beams, including beam flatness, symmetry, percent depth dose (PDD), output factor and MU linearity, were investigated. Flatness and symmetry were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Halcyon 2.0 contains a fixed MLC sequence that flattens the 6FFF beam by sweeping the proximal MLCs while the beam is delivering dose to provide a flattened beam profile (dynamically flattened beam, DFB). [12][13][14] The distal MLCs define the treatment field.…”
Section: A | Halcyon 20mentioning
confidence: 99%
“…Halcyon 2.0 contains a fixed MLC sequence that flattens the 6FFF beam by sweeping the proximal MLCs while the beam is delivering dose to provide a flattened beam profile (dynamically flattened beam, DFB). [12][13][14] The distal MLCs define the treatment field.…”
Section: A | Halcyon 20mentioning
confidence: 99%
“…Halcyon™ (Varian Medical Systems, Palo Alto, CA, USA), a novel 6 megavolt (MV)-flatteningfilter-free (6X-FFF) O-ring gantry linac, was built to administer RT with greater speed and throughput than a C-arm linac (CAL), with some similarities to TomoTherapy (Accuray, Sunnyvale, CA, USA) [14]. Published reports of 6X-FFF O-ring linacs (ORL) are largely limited to pre-clinical planning studies, and have demonstrated similar plan quality with faster calculated treatment times for 6X-FFF ORLs versus CALs [14][15][16][17][18][19]. Reports of the clinical use of a 6X-FFF ORL to date have been limited to breast cancer [20], gynecologic cancers [12], and malignant pleural mesothelioma (MPM) [21], and have demonstrated fast treatment times and high throughput with the 6X-FFF ORL compared to CALs, with comparable plan quality, toxicity, and early disease-control.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the Halcyon can perform reference dosimetry without a specialized chamber or lead filtering chamber and is well suited for resource-limited units. Bollinger et al [12] studied the dosimetric features and limitations of the dynamic flattening beam on the Halcyon 2.0 and found that the transversal and radial profiles of ≥10 cm square fields were observed with <3% flatness under the conditions of 100 cm SSD and 10 cm water depth. The positioning accuracy of MLC, gantry angle, and couch shift were within 0.05 mm, 0.02°, and 0.03 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%